A Novel Targeted Analysis of Peripheral Steroids by Ultra-Performance Supercritical Fluid Chromatography Hyphenated to Tandem Mass Spectrometry. Issue 1 (December 2018) - de Kock, Neil; Acharya, Santosh; Ubhayasekera, S.; Bergquist, Jonas
Abstract Ultra-performance supercritical fluid chromatography–tandem mass spectrometry (UPSFC–MS/MS) is an alternative method for steroid analysis. Continuous development of analytical methodologies for steroid profiling is of major importance in the clinical environment to provide useful and more comprehensive data. The aim of this study was to identify and quantify a large number of endogenous steroids from the four major classes (estrogens, androgens, progestogens and corticosteroids) simultaneously within a short analytical time. This novel UPSFC–MS/MS method with electrospray in positive ionisation (ESI+) mode is robust, selective and present sufficiently high sensitivity to profile nineteen steroids in 50 µL human plasma. Under optimised conditions, nineteen different steroids were separated with high efficiency in the multiple reaction monitoring (MRM) mode. The linearity of the method was good with correlation coefficients (R2 ) in the range of 0.9983–0.9999 and with calibration range from 0.05–500 ng/mL in human plasma. The intraday and interday precision of the method, as RSD, was less than 15%. The accuracy of the nineteen analytes varied between 80 to 116%. Finally, the novel method was successfully applied for the determination of nineteen steroids within 5 minutes providing the possibility to use it for research as well as routine healthcare practice.